Gallium and indium complexes containing the bis(imino)phenoxide ligand: synthesis, structural characterization and polymerization studies1. Issue 22 (14th June 2015) - Ghosh, Swarup; Gowda, Ravikumar R.; Jagan, Rajamony; Chakraborty, Debashis
<x xml:space="preserve">Abstract</x> A series of gallium and indium complexes containing the bis(imino)phenolate ligand framework were synthesized and completely characterized with different spectroscopic techniques.